2015 ATVB Plenary Lecture: Translational Research on Rho-Kinase in Cardiovascular Medicine. Issue 8 (August 2015) - Shimokawa, Hiroaki; Satoh, Kimio
Abstract : Rho-kinase (ROCKs) is an important downstream effector of the small GTP-binding protein Ras homolog gene family member A. There are 2 isoforms of ROCK, ROCK1 and ROCK2, and they have different functions in several vascular components. The Ras homolog gene family member A/ROCK pathway plays an important role in various fundamental cellular functions, including contraction, motility, proliferation, and apoptosis, whereas its excessive activity is involved in the pathogenesis of cardiovascular diseases. For the past 20 years, a series of translational research studies have demonstrated the important roles of ROCK in the pathogenesis of cardiovascular diseases. At the molecular and cellular levels, ROCK upregulates several molecules related to inflammation, thrombosis, and fibrosis. In animal experiments, ROCK plays an important role in the pathogenesis of vasospasm, arteriosclerosis, hypertension, pulmonary hypertension, and heart failure. Finally, at the human level, ROCK is substantially involved in the pathogenesis of coronary vasospasm, angina pectoris, hypertension, pulmonary hypertension, and heart failure. Furthermore, ROCK activity in circulating leukocytes is a useful biomarker for the assessment of disease severity and therapeutic responses in vasospastic angina, heart failure, and pulmonary hypertension. In addition to fasudil, many other ROCK inhibitors are currently under development for various indications. Thus, the ROCK pathway is an important novel therapeutic target in cardiovascular medicine.